2009
DOI: 10.1073/pnas.0907117106
|View full text |Cite
|
Sign up to set email alerts
|

Statins inhibit protein lipidation and induce the unfolded protein response in the non-sterol producing nematode Caenorhabditis elegans

Abstract: Statins are compounds prescribed to lower blood cholesterol in millions of patients worldwide. They act by inhibiting HMG-CoA reductase, the rate-limiting enzyme in the mevalonate pathway that leads to the synthesis of farnesyl pyrophosphate, a precursor for cholesterol synthesis and the source of lipid moieties for protein prenylation. The nematode Caenorhabditis elegans possesses a mevalonate pathway that lacks the branch leading to cholesterol synthesis, and thus represents an ideal organism to specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 45 publications
(55 reference statements)
7
71
3
2
Order By: Relevance
“…It seems likely that inhibition of protein prenylation should impact many cellular processes and organelles besides the mitochondria. Indeed, statins strongly induce the UPR er in C. elegans, suggesting not only that the endoplasmic reticulum is impacted by inhibition of the mevalonate pathway, but also that the cell is able to activate an appropriate stress response (9). The mitochondrial stress caused by statins is therefore unusual in that it does not result in the activation of UPR mt even though it is evidently the required protective response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems likely that inhibition of protein prenylation should impact many cellular processes and organelles besides the mitochondria. Indeed, statins strongly induce the UPR er in C. elegans, suggesting not only that the endoplasmic reticulum is impacted by inhibition of the mevalonate pathway, but also that the cell is able to activate an appropriate stress response (9). The mitochondrial stress caused by statins is therefore unusual in that it does not result in the activation of UPR mt even though it is evidently the required protective response.…”
Section: Discussionmentioning
confidence: 99%
“…Plates with different concentrations of fluvastatin (brand Lescol; Novartis) were made as described in a previous study (9). Briefly, 40 mg of fluvastatin was dissolved in water (2.31 mL) and spun at 5,000 × g to separate insoluble components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is indirect evidence, previous studies have shown that statin treatment increases IDE secretion, and inhibits protein prenylation. 35,41 Whether IDE secretion by statin treatment occurs through same pathway as Ab treatment should be investigated. Further, how IDE inside the lysosome is transported to the extracellular medium needs to be determined.…”
Section: Discussionmentioning
confidence: 99%